Shelf-Life Evaluation of a Novel Functional Product from a Blend of Powdered Vegetables - Aisha Idris Ali; Virginia Paul; Munir Abba Dandago; Fatima Idris Ali; Daniel Amiteye (Turkish Journal of Agriculture: Food Science and Technology)
Perishable fresh vegetables that do not meet cosmetic standards and other crop waste rich resources are presently wasted. Mangifera indica leaves, Psidium guajava leaves, Petroselinum crispum leaves and Daucus carota were selected as model vegetables to show that they can be converted into a shelf-stable novel functional powdered product. A novel functional product from a blend of these powdered vegetables (FPPV) was formulated. To evaluate the shelf-life of FPPV. The novel functional product from a blend of powdered vegetables (FPPV) was prepared in the Food Science and Nutrition laboratory, Sam Higginbottom University of Agriculture Technology and Sciences, India. The samples were subjected to accelerated stability study maintaining temperature and relative humidity 40°C ± 2°C and 75% ± 5% respectively. Organoleptic, physico‑chemical and microbiological properties of FPPV was analyzed at an interval of 0, 1, 3 and 6 months to check the degradation levels in the formulation. Organoleptic characters showed no significant changes in accelerated stability condition. There were insignificant changes in physico-chemical profiles and product was free from microbial contamination at different intervals of analysis. On extrapolation of the observations the shelf-life of FPPV was found to be 51 months (4 years and 3 months) for climatic zone I & II countries and 34 months (2 years and 10 months) for climatic zone III & IV countries, respectively. The conversion of perishable vegetables and crop wastes into shelf-stable functional food products will reduce food loss and waste in the vegetable industry.